Snappsy the alligator and his best friend forever (probably) - Falatko, Julie (Viking, an imprint of Penguin Random House, LLC, 2017)
Snappsy the alligator wants to spend a quiet evening reading, but a pesky chicken who insists he is Snappsy's best friend will not leave him alone.